ASI Ekslusif, Perilaku Orang Tua Dalam Pemberian Makan Dan Kejadian Stunting Pada Anak Usia 1-3 Tahun - Ni Luh Agustini Purnama (Jurnal Keperawatan Muhammadiyah, 2021)
Stunting is one of the nutritional problems that occur in toddlers due to chronic malnutrition. Chronic malnutrition is closely related to the ineffectiveness of exclusive breastfeeding, poor parenting, especially the behavior of mothers in feeding toddlers, this is because mothers have a major role, especially in choosing and preparing food to be consumed by toddlers. The phenomenon that occurred at the Posyandu Anggrek, Mulyorejo, Surabaya, was found that some children had a height that was not suitable for their age and some parents only gave formula milk when the child did not want to eat. The purpose of this study was to analyze the relationship between exclusive breastfeeding, parental behavior in feeding toddlers with stunting. The study design uses a cross-sectional design. Respondents were 22 mothers in Posyandu Anggrek 2, Mulyorejo Subdistrict, Surabaya, who fulfilled the inclusion and exclusion criteria. Stunting in toddlers is assessed based on z-score Height/ Age. Exclusive breastfeeding was assessed using a questionnaire. Maternal behavior in feeding is measured using the Parental Feeding Behaviors Questionnaire (PFBQ) questionnaire. Fisher's Exact Test statistic test results show there is a relationship between exclusive breastfeeding and parental behavior in feeding children with stunting in children aged 1-3 years (p = 0.002; p = 0.015). Exclusive breastfeeding and proper feeding behavior are important to prevent stunting in children.